The Gender Role and Sustainable Agriculture Practice of Sugar Palm Farmers in Enrekang Highland, South Sulawesi - Hardiansyah M, Muhammad Arfan; Tubangsa, Ian (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2025)
This paper explores the sustainable agricultural practices of sugar palm farmers in the highlands of Enrekang, South Sulawesi, which have been given less attention by modern agricultural policies. Sustainable agriculture is a solution to the negative impacts caused by conventional agricultural systems. Using holistic approach, this paper aims to reveal how traditional sugar palm cultivation can contribute to sustainable agriculture from economic, social, and environmental aspects. The research method is qualitative research using indepth interviews and observations of farmer households and comparing the findings with other supporting secondary documents. The research findings show that the economic aspects of sustainable agriculture are seen through the processing and production efficiency of palm sugar which is widely practiced to be able to provide decent economic benefits for farmers. From the social aspect, the utilization of sugar palm crops also shows the existence of gender roles and access opportunities to resources for local communities. From an environmental aspect, sustainable practices are reflected through the use of eco-friendly packaging by Enrekang palm sugar products and the presence of sugar palm contributes to the conservation of land, water and biodiversity in the highland area. The government needs to focus on sustainable agricultural policies such as the utilization and developed of sugar palm crops in the highlands involving local farmers.